ANALISIS PENGARUH PDB DAN KURS DOLLAR AMERIKA TERHADAP NERACA PERDAGANGAN MELALUI FOREIGN DIRECT INVESTMENT DI INDONESIA TAHUN 1996-2015 - Putri, Novi Hasana; Arka, Sudarsana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; vol.6.No. 9. September 2017(pp.1628-1867), 2017)
ABSTRACT International trade is a an economic activitiy to trade  and exchange  goods and services with other countries. This study aims to determine  direct influences and indirect influence among  variables which become  object research, namely GDP, Exchange Rate (US Dollar), FDI and trade balance in Indonesia. D ata used are secondary data from 1996 to 2015. Data analysis technique used is path analysis with  assistment of  SPSS 16.00 program. Based on  results of  analysis, GDP variable has a positive effect on foreign direct investment, variable of US Dollar exchange rate has negative effect on foreign direct investment, GDP has negative effect on trade balance, US dollar exchange rate has positive effect on trade balance and FDI has no effect on trade balance. GDP and US dollar exchange rate have no indirect effect on trade balance through FDI in Indonesia in 1996-2015. Keywords: Exchange Rate US Dollar, foreign direct investment, GDP, trade balance